Breathing-With Other-Than-Humans - Tu, Steve 4. (Imaginations)

(untitled) (York University, 2024)
This paper outlines part of a research-creation project focused on human/tree communication on a specific campus green space of a Canadian university. As part of a multispecies ethnographic study of the university, I explore the reciprocal relationship between humans and trees via multispecies duoethnography, a method I am pioneering that draws on time, breathing-with, imagination, and artistic expression. I surface some nuances of interspecies communion, specifically emphasizing the role of breath in moving from acts of attentiveness to frequencies of attunement with arboreal beings.